Isolectins from Sambucus nigra fl owers and their effect on MGMT and P53 proteins amount in human cells in vitro - Lylo, V.V.; Karpova, I.S.; Kotsarenko, K.V.; Macewicz, L.L.; Ruban, T.A.; Dziuba, G.V.; Lukash, L.L. (Фактори експериментальної еволюції організмів, 2015)
Aim. To characterise S.nigra fl ower isolectins in the aspect of their effect on MGMT and p53 proteins amount. Methods. Lectin preparations P1, P2 and P3 with defferent pI were obtained by isoelectric focusing. The Hep-2 cells were treated with S. nigra lectins: P1, P2, and a commercial SNA-I. Changes of protein amounts were detected by Western blot analysis. Results. Isolectins were characterized accoding to their carbohydrate specificity. They increased MGMT amount with different severity. p53 level under the P2 and SNA-I treatments reduced. These lectins were shown to effect the amount of MARP protein as well. Conclusions. All lectins studied enhanced the amount of MGMT and MARP proteins. Effect of lectins on p53 amount was the opposite. MGMT is supposed to be the primary target of lectin action which uses own lectin-dependent regulatory pathways of mammalian cells, and p53 level may be affected as a result of MGMT modulation.